Rancang Bangun Aplikasi Biro Travel dengan SMS Gateway dan Google Maps API - At Taufiq, Muhammad Hazbiallah; Hidayati, Anita (POLITEKNIK NEGERI JAKARTA, 2016)
Let's Go Outside Travel is a company engaged in the service. Services offered are open-trip travel and tours combined. Tours provided by the travel easier for customers to travel schedules and facilities that are already programmed. The technology can help this is to develop a web-based system for travel agencies Let's Go Outside in the promotion. To meet the demands of the importance of managing the data do the booking, the travel party decided to create a web application that serves to promote new tourism by using google maps API, add a photo documentation and facilitate the process of confirming the transaction with SMS Gateway technology. These include web application design business processes in the travel Let's Go Outside. This design using waterfall method. This method uses a real way and clear for every step of the manufacturing system. The web applications created using CodeIgniter framework, the application has been undergoing testing stages. The results showed that the application has been successfully meeting the user needs with the success rate is 85.7% of 13 respondents.